Influence of the indigenous gastrointestinal microbial flora on duodenal Mg2+ -dependent and (Na+ + K+) -stimulated adenosine triphosphatase activities in mice. - Yolton, D P (1976)
Mg-dependent and (Na+ + K+)-stimulated adenosine triphosphatase (ATP-ase) activities were assayed in butanol extracts of duodenal tissue from germ-free, specific-pathogen-free, and ex-germfree mice associated with an indigenous microflora from specific-pathogen-free mice. In the germfree mice the levels of both ATPase activities were significantly higher than the levels in specific-pathogen-free mice. By contrast, the ex-germfree animals colonized by an entire indigenous microflora, the values fell to levels close to those for specific-pathogen-free animals. (Na+ + K+)-stimulated ATPase was not inhibited by ouabain in extracts from any of the three kinds of mice. These findings show that the indigenous microbial flora influences the intestinal ATPase activity of mice and, because of the connection between (Na+ + K+-stimulate ATPase and active transpoort, undoubtedly affects the process of absorption in the intestinal tract.